Innovations In Learning Management To Foster Student Creativity - Sukirdi Sukirdi; Feby Elra Perdima; Jumiati Siska; Fenty Hanifa Carolina (Lembaga Bale Literasi, 2025)
Creativity has become a strategic learning outcome in contemporary schooling, yet many classroom innovations remain fragmented because management practices are rarely examined as an integrated mechanism that shapes the learning climate, teacher coordination, assessment design, and student agency. This study aims to analyze how innovative learning management contributes to the development of student creativity and to clarify whether creative learning climate and student engagement mediate this relationship. An explanatory sequential mixed-methods design was proposed. The quantitative phase involved 312 secondary-school students selected through cluster sampling, while the qualitative phase involved interviews with 12 teachers and six school leaders. Data were collected using a learning management innovation scale, a creative learning climate scale, a student engagement scale, and a portfolio-based creativity rubric covering fluency, flexibility, originality, and elaboration. The illustrative analysis using partial least squares structural equation modelling indicated that innovative learning management had a positive direct effect on student creativity (beta = .31, p < .001) and stronger indirect effects through creative learning climate and engagement. The model explained 61% of the variance in student creativity, suggesting that creativity is not merely a product of individual talent but is also shaped by managerial decisions that organize time, feedback, collaboration, and assessment opportunities. The findings imply that schools should move beyond episodic innovation and institutionalize learning management systems that protect experimentation, support teacher collaboration, and use formative assessment to cultivate creative performance.